PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PRODUKSI DI PT. BUANA TUNAS SEJAHTERA - Dimas Priyo Cristian; R Sesario; T.C.W.A Sutignya (Jurnal Agro Estate, 2021)
Compensation and job satisfaction are factors that affect employee performance in achieving a company's goals. Employee performance is one of the factors that influence a company's success rate. This study aims to determine the effect of compensation and job satisfaction on the performance of production employees at PT. Buana Tunas Sejahtera. The purpose of this study was to discover the effect of compensation and job satisfaction on the performance of PT. Buana Tunas Sejahtera Seriang Mill located in Kapuas Hulu Regency, Badau District. The Multiple Linear Regression uses Analysis with a sample of 30 respondents production employees. Research analysis tool is a questionnaire with a Likert scale using SPSS version 22. The results in this compensation study did not affect employee performance with negative t test results, then job satisfaction had a significant effect on employee performance with positive T test results. Compensation and job satisfaction together have a significant positive effect on employee performance.